Ecological footprint mitigation through corporate environmental management: Measuring carbon sequestration in PT Organon Pharma Indonesia's conservation and industrial areas - Ardiansyah, Reza; Nugroho, Endik Deni; Ainiyah, Roisatul; Fathurrohman, Amang; Matrani; Pasaribu, Aswin; Nur'aini, Afifah Diyah; Prayitno, Trio Ageng (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Climate change mitigation in the pharmaceutical industry is necessary for corporate conservation. This study aims to measure the carbon sequestration potential in the conservation area and the Seroto Block plantation area, evaluate the company's environmental management strategy, and analyze the success factors of the conservation program at PT Organon Pharma Indonesia. This study uses a mixed-methods approach with a sequential explanatory design. The research instruments include GPS, tree measuring tools, environmental sensors, and biomass assessment tools. Data analysis techniques include estimating biomass per tree, determining carbon stocks, calculating CO₂ equivalents, and evaluating the effectiveness of conservation strategies. The results show that the conservation area stores the most carbon (a total of 40.39 tons C/ha, equivalent to 462.56 tons CO₂), followed by the industrial area (a total of 10.77 tons C/ha, equivalent to 95.55 tons CO₂), and the plantation area shows minimal carbon storage (60.95 kg). Pinus merkusii dominated the conservation area (85.6% of carbon storage), while Mangifera indica, Pterocarpus indicus, and Filicium decipiens contributed 91.5% of carbon storage in the industrial area. Environmental conditions, which were optimal in the conservation area (24.3°C, 73% humidity, pH 6.3) and harsher in the industrial area (33.3°C, 56% humidity), had a significant impact on carbon sequestration. This study concluded that conservation areas have the highest carbon storage capacity compared to industrial and plantation areas.